Environmental educational actions in the community: a necessary look for a change (Original) (REDEL. Revista Granmense de Desarrollo Local, 2019)
The work result is part of one of the directions of the Community Extension Project: "The spirituality in the senile ages developed in the educational subsidiary of Bayamo", which was aimed at favoring the preservation and development of culture in people of third age from the Popular Council: San Juan, El Cristo, through educational actions, focused on non-formal environmental education for the solution of environmental problems of the community, actions carried out by university students favoring the development of professional skills, human sensitivity and quality in comprehensive training, to confront the challenges of the profession related to environmental education.
Keywords: community extension project; non-formal environmental education; environmental problems; comprehensive training.